2015
DOI: 10.4103/1658-354x.159471
|View full text |Cite
|
Sign up to set email alerts
|

Femoral nerve block for acute pain relief in fracture shaft femur in an emergency ward

Abstract: Background:Analgesia in patients with fracture shaft femur is usually insufficient as physician usually relies on parental analgesia in such situations. Local anesthetic blockade of femoral nerve to provide analgesia in fracture shaft femur is an under-used technique. We conducted a study to evaluate the efficacy of femoral nerve block (FNB) with 0.5% ropivacaine for acute pain relief in patients with fracture shaft femur.Materials and Methods:A total of 50 patients were studied as they present in an emergency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Application of these results to patients with femoral shaft and distal fractures should be done with caution. Somvanshi et al [15] also reported that pain scores significantly decreased, but the quality of analgesia did not change when patients underwent a radiological examination and traction application after femoral nerve block in patients with fracture of the femur shaft in the emergency ward.…”
Section: Discussionmentioning
confidence: 99%
“…Application of these results to patients with femoral shaft and distal fractures should be done with caution. Somvanshi et al [15] also reported that pain scores significantly decreased, but the quality of analgesia did not change when patients underwent a radiological examination and traction application after femoral nerve block in patients with fracture of the femur shaft in the emergency ward.…”
Section: Discussionmentioning
confidence: 99%
“…In the non-surgical adult population, using a prospective, randomized, but non-blinded study protocol, regional anesthetic techniques (3-in-1 block or FNB) have been shown to decrease morphine requirements and lower pain scores when compared to use of opioids alone. 13 15 In a non-blinded, prospective, randomized study in a non-surgical population, Wathen et al reported lower pain scores in pediatric patients with a femur fracture who received a fascia iliaca compartment nerve block in the ED when compared to intravenous morphine. 16 When comparing the entire 6-h study period pain scores, pain scores were approximately 15% lower in patients who received a fascia iliaca compartment nerve block.…”
Section: Discussionmentioning
confidence: 99%
“…preoperative baseline VAS scores as observed in our study and described in other studies. 1,4 Paracetamol, ketamine, non-steroidal anti-inflammatory drugs, or opioids have been used to relieve pain during positioning, but have their limitations. 2,3 The femoral nerve block, a simple and easy to perform procedure, has been used both pre-emptively as well as post-operatively for fracture femur surgeries, anterior aspect of thigh or knee surgeries, or for physiotherapy after knee surgery.…”
Section: Group Us (N = 30)mentioning
confidence: 99%
“…Fracture femur pain is a painful condition that often gets intolerable on movement especially during shifting, positioning during regional anesthesia or radiological evaluation. 1 Various drugs are used for its management, such as nonsteroidal anti-inflammatory drugs or intravenous opioids, but, each has its limitations and side effects. Recently, femoral nerve block (FNB) which can be given either by using a nerve stimulator or under ultrasound guidance, has gained popularity.…”
Section: Introductionmentioning
confidence: 99%